DEVELOPMENT OF NEW NANO COMPOSITE ELECTROLYTE Ag/AgI/Ag BY PVD TECHNIQUE - E. Kartini; S. Nikmatin; S. Suminta; A. Handayani (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
DEVELOPMENT OF NEW NANO COMPOSITE ELECTROLYTE Ag/AgI/Ag BY PVD TECHNIQUE. A new composite electrolyte Ag/AgI/Ag has been developed by Physical capour deposition (PVD) technique. Ag have been deposited on both sides of the coin type- superionic conductor AgI with deposition times 30, 45 and 60 minutes. Several characterizations on deposited Ag/AgI/Ag such as the crystal structure, micro structure, hardness, density, and ionic conductivity have been performed by useing respectively, an X-Ray Diffractrometer, Scanning Electron Microscope/EDAX, Micro Hardness Tester, Pycnometer and Impedance Spectroscopy. The x-ray pattern at room temperaturer for deposited Ag/AgI/Ag does not show any phase transformation and the structure is dominated by γ-AgI, with the particle size is about 27.3 nm. There is a significant increase in ionic conductiviyu from 10-6 S/cm to 10-3 S/cm. The increase of the ionic conductivity is possibly due to the increasing number of Ag from 48.62% to 64.04% in the new composite Ag60'/AgI/Ag60' as comfirmed by the result from EDAX. The microstructure measured by SEM shows an expansion of the matrix AI after deposited by Ag. With increasing deposition time, the hardness increases, while the density descreases.